BIODIESEL PRODUCTION FROM BLACK SOLDIER FLY (HERMETIA ILLUCENS) LARVAE VIA IN SITU INTERESTERIFICATION IN A STIRRED TANK REACTOR SYSTEM WITH BIOCATALYST FROM RHIZOPUS ORYZAE - Zaki Arrazi, Muhammad
As a solution to energy and environmental problems, biodiesel can be produced using biomass from black soldier fly larvae (BSFL) as a source of animal oil, thus avoiding conflict with the food sector. However, in biodiesel production, the use of chemical or acid catalysts can cause problems, such as the formation of soap in the transesterification process, damage to equipment due to corrosion, the production of large amounts of waste water, and difficulties in the separation of catalysts dissolved in biodiesel. Therefore, the use of lipase enzyme from Rhizopus oryzae biocatalyst with loofah matrix can avoid negative impacts on the environment because it can be used repeatedly and does not cause difficult separation with the biodiesel produced. This study aims to synthesize and determine the enzymatic activity of Rhizopus oryzae wild-type biocatalyst and compare with commercial lipase, design a stirred tank reactor for biodiesel production, determine the effect of reaction time on the yield of biodiesel produced in-situ from BSFL with methyl acetate solvent at variations of reaction time of 4, 8, 12, 16, 20, 24, and 28 hours, and determine the composition of biodiesel, and quality parameters of biodiesel produced from optimum conditions in stirred tank reactor (STR) system. The enzymatic activity of the synthesized Rhizopus oryzae whole-cell biocatalyst resulted in a value of 4014.945 U/g which was higher than that of commercial lipase enzymes. The biodiesel yield value as a function of reaction time from the in-situ extraction and interesterification process using methyl acetate solvent produces an increasing yield profile up to 20 hours reaction time and tends to stagnate at 24 to 28 hours reaction time with the highest biodiesel yield of 94,59% obtained when the reaction time is 20 hours, the stirring speed is 180 rpm, and the reaction temperature is 37?. The composition of biodiesel includes FG (free glycerol), MAG (monoglycerides), DAG (diglycerides), TAG (triglycerides), and esters obtained respectively by : 0,023%; 0,102%; 5,218%; 0,071%; and 94,586%. Then, the quality of biodiesel in the optimum reaction conditions, in the form of water content, density, kinematic viscosity, and HHV values have values of: 0,037%; 882,622 kg/m3; 3,539 mm2/s; and 40,689 MJ/kg. In this study, it was found that the synthesis of lipase enzyme from Rhizopus oryzae wild-type biocatalyst using loofah matrix showed good results through higher enzymatic activity values than commercial lipase and biodiesel quality that met SNI 7182: 2015 and EN 14214 standards